A Global Geospatial Ecosystem Services Estimate of Urban Agriculture. Issue 1 (10th January 2018) - Clinton, Nicholas; Stuhlmacher, Michelle; Miles, Albie; Uludere Aragon, Nazli; Wagner, Melissa; Georgescu, Matei; Herwig, Chris; Gong, Peng
Abstract: Though urban agriculture (UA), defined here as growing of crops in cities, is increasing in popularity and importance globally, little is known about the aggregate benefits of such natural capital in built‐up areas. Here, we introduce a quantitative framework to assess global aggregate ecosystem services from existing vegetation in cities and an intensive UA adoption scenario based on data‐driven estimates of urban morphology and vacant land. We analyzed global population, urban, meteorological, terrain, and Food and Agriculture Organization (FAO) datasets in Google Earth Engine to derive global scale estimates, aggregated by country, of services provided by UA. We estimate the value of four ecosystem services provided by existing vegetation in urban areas to be on the order of $33 billion annually. We project potential annual food production of 100–180 million tonnes, energy savings ranging from 14 to 15 billion kilowatt hours, nitrogen sequestration between 100, 000 and 170, 000 tonnes, and avoided storm water runoff between 45 and 57 billion cubic meters annually. In addition, we estimate that food production, nitrogen fixation, energy savings, pollination, climate regulation, soil formation and biological control of pests could be worth as much as $80–160 billion annually in a scenario of intense UA implementation. Our results demonstrate significant country‐to‐country variability in UA‐derived ecosystem services and reduction of food insecurity. These estimates represent the first effort to consistently quantify these incentives globally, and highlight the relative spatial importance of built environments to act as change agents that alleviate mounting concerns associated with global environmental change and unsustainable development. Key Points: We present an original, data‐driven approach to quantify country‐scale multifunctionality of urban agriculture (UA) adoption We estimate that UA can provide a range of ecosystem services, which highlights the role of built environments for increasing adaptive capacity to climate change We estimate that China, Japan, Germany, and the United States have a suitable combination of factors to be consistently among the top beneficiaries of UA in terms of estimated dollar potential and associated ecosystem services